Design of a Device for Disinfection of Paper Money in ATMS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In the modern world, the active use of paper money increases the risk of spreading infectious diseases through microorganisms and viruses. This is especially true for banknotes passing through ATMs, as they come into contact with a large number of users. Therefore, the development of an effective and automated mechatronic device for disinfecting paper money in ATMs is an urgent task.During the research, existing disinfection methods were studied, their advantages and disadvantages were analyzed, and the most optimal method was selected, ensuring the cleaning of banknotes without damaging their structure. The device may use ultraviolet (UV) radiation, heat treatment, or chemicals. It is integrated into the ATM's design and automatically disinfects the money during the process of dispensing and receiving.The proposed development aims to improve user safety, ensure sanitary standards, and enhance the hygienic reliability of banking operations. The study examines the mechanisms of the device, its efficiency, and the possibilities for practical application.